Distinguishing Voice and Silence at Work: Unique Relationships with Perceived Impact, Psychological Safety, and Burnout - Sherf, Elad N.; Parke, Michael R.; Isaakyan, Sofya (Academy of Management Journal, 2021)
Scholars continue to debate whether voice and silence are opposites or distinct constructs. This ambiguity has prevented meaningful theoretical advancements about employees’ voice and silence at work. We draw on the behavioral activation and behavioral inhibition systems perspective to provide a conceptual framework for the independence of voice and silence and explicate how two key antecedents—perceived impact and psychological safety—more strongly relate to voice and silence, respectively. We further differentiate voice and silence by identifying their distinct effects on employee burnout. In Study 1, a meta-analysis, we demonstrate that voice and silence are independent (Mρ = −.15) and that perceived impact (psychological safety) relates more strongly to voice (silence) than to silence (voice). We also find that silence has a significantly stronger association with burnout compared to voice. In Study 2, we constructively replicate these findings in an interval-contingent panel study across six months. Taken together, this article helps shift the conversation of whether voice and silence are distinct constructs to how they differ and why such differences matter.